2010
DOI: 10.4314/tjpr.v9i3.56284
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between phenothiazines and oxacillin against clinical isolates of methicillin-resistant <i>Staphylococcus aureus</i>

Abstract: Purpose: To evaluate the antimicrobial and resistance-reversal activities of seven phenothiazine derivatives against one standard methicillin-sensitive and ten methicillin-resistant Staphylococcus aureus (MRSA) strains originating from human infections. Methods: Minimum inhibitory concentrations (MIC) of the compounds were determined by agar dilution method, and synergy between phenothiazines and oxacillin was investigated using Checkerboard (microbroth dilution) technique. Results: We found that all S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(23 reference statements)
3
3
0
Order By: Relevance
“…Regarding zones of growth inhibition against MRSA, trifluoperazine produced 0, 13, 18-and 26-mm zone of growth inhibition at 25, 50, 75 and 100 µg/disc potency respectively. These findings are in line with the studies conducted previously (Hadji-nejad et al, 2010 andAmaral et al, 2004). This antimicrobial activity of trifluoperazine against this MRSA isolate is attributed to property of phenothiazine to inhibit ABC type efflux pumps that account for the antibiotic resistance of the organism.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding zones of growth inhibition against MRSA, trifluoperazine produced 0, 13, 18-and 26-mm zone of growth inhibition at 25, 50, 75 and 100 µg/disc potency respectively. These findings are in line with the studies conducted previously (Hadji-nejad et al, 2010 andAmaral et al, 2004). This antimicrobial activity of trifluoperazine against this MRSA isolate is attributed to property of phenothiazine to inhibit ABC type efflux pumps that account for the antibiotic resistance of the organism.…”
Section: Discussionsupporting
confidence: 94%
“…MICs determined against the said isolates were 50µg/ml for MRSA and P. aeruginosa, whereas it was 100 µg/ml for E. coli. This MICs obtained for trifluoperazine are in line with the studies conducted previously (Hadji-nejad et al, 2010;Advani et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown that thioridazine can reverse resistance to oxacillin (a methicillin analogue), if the two drugs are used in combination against MRSA in vitro (Klitgaard et al ., 2008). This synergy, which restores susceptibility to oxacillin, has been confirmed in 10 clinical isolates by others (Hadji‐nejad et al ., 2010). Thioridazine is a phenothiazine derivate, which has been shown to have therapeutic applications in problematic infections caused by antibiotic‐resistant bacteria (Amaral et al ., 2004).…”
Section: Introductionsupporting
confidence: 68%
“…Such as the LAR-1 algorithm (Hnatyshin, 2013;Husain et al, 2010;Deb et al, 2009) and probabilistic broadcast (Hadji-nejad et al, 2010;Nand and Sharma, 2012;Al-Bahadili, 2010a;AlBahadili and Kaabneh, 2010).…”
Section: Jcsmentioning
confidence: 99%
“…The performance of the new model was compared against pure and probabilistic algorithms. Hadji-nejad et al (2010) introduced a routing scheme for MANETs, which works well under a wide range of network topologies, nodes-density, coverage area size Science Publications JCS and nodes-mobility. The scheme is based on a novel enhancement of the hint-based probabilistic protocol.…”
Section: Jcsmentioning
confidence: 99%